Imitação e diferença em Gabriel Tarde - Monzelli, Arthur Guilherme (Laboratório Editorial Faculdade de Ciências e Letras, 2016)
We intend, by this reflexion, to focus on some principles of a sociological theory which, unfortunately, was renegade to the limbo of the social sciences, condemned to be apreciated only by the “gnawing criticism of the mice”. We refer to sociological theory developed by Gabriel Tarde. Being more specific, our focus will the tardian notion imitation and how it shows itself the founder pillar of his notion of the society. At last, we will articulate our reflexion with our own social historical context of formation, in order to find out substrates to the explanation of Tarde’s sociological perspective. In this sense, we refer to music, specifically to the rap of Racionais Mc’s and the popular notion of social organization self-titled Bonde.